Lower prevalence of subsegmental pulmonary embolism after application of the YEARS diagnostic algorithm - Pol, Liselotte M.; Bistervels, Ingrid M.; Mens, Thijs E.; Hulle, Tom; Beenen, Ludo F. M.; Exter, Paul L.; Kroft, Lucia J. M.; Mairuhu, Albert T. A.; Middeldorp, Saskia; Werkhoven, Jaap M.; Wolde, Marije; Huisman, Menno V.; et al. (British journal of haematology, 2018)
Summary The rate of identified isolated subsegmental pulmonary embolism (ssPE) has doubled with advances in computed tomography pulmonary angiography (CTPA) technology, but its clinical relevance is debated. The YEARS diagnostic algorithm was shown to safely reduce the number of required CTPAs in the diagnostic management of PE. We hypothesized that the higher threshold for performing CTPA in YEARS was associated with a lower prevalence of ssPE compared to the conventional diagnostic algorithm. We compared 2291 consecutive patients with suspected PE managed according to YEARS to 3306 consecutive control patients managed according to the Wells score for the prevalence of isolated ssPE. In the YEARS cohort, 52% were managed without CTPA, 12% had pulmonary embolism (PE) of which 10% were isolated ssPE, and the 3‐month diagnostic failure rate was 0·35%. In the control cohort, 32% were managed without CTPA, 20% had PE of which 16% were isolated ssPE, and the 3‐month failure rate was 0·73%. The isolated ssPE prevalence was significantly lower in YEARS (absolute difference 6·2% (95% confidence interval [CI] 1·4–10), Odds Ratio 0·58 (95% CI 0·37–0·90). In conclusion, YEARS is associated with a lower prevalence of isolated ssPE, due to reduction in CTPAs by the higher D‐dimer threshold. This was however not associated with a higher risk of recurrent VTE during follow‐up.